Water security in a changing world - Giordano, Meredith (2018)
Meredith Giordano POLICY SEMINAR Water Security in a Changing World Co-Organized by International Water Management Institute (IWMI) and IFPRI JUL 12, 2018 - 09:30 AM TO 11:00 AM EDT